Las dos versiones argentinas de Sodoma y Gomorra y La prisionera de Marcel Proust: semejanzas y diferencias (incluso de dialectología léxica) - Herbert E. Craig (Catalonia)
Volumes four and five of the Recherche, Sodome et Gomorrhe and La prisonnière, were translated for the first time to Spanish by the Argentine Marcelo Menasché. When Santiago Rueda published the seventh and last volume in 1946, this series became the second foreign complete edition in the world (after the English one, 1922-1931). Nonetheless Menasché’s translation was severely criticized for being «de una literalidad exasperante» (Emir Rodríguez Monegal, Uruguay) and for being «plagada de argentinismos» (José Luis Cano, Spain).Losada of Buenos Aires began in 2000 to publish a new translation by Estela Canto. This publisher would claim that this Argentine writer had translated before her death in 1994 all but the last volume. In my analysis of Sodoma y Gomorra, I will show that the translation by Canto is different from and better than that of Menasché, but that his is not appreciably worse than the versions created in Spain during those years. On the other hand, despite the attribution by Losada to Canto of the translation of La prisionera, I assert that the same errors, omissions and Argentine expressions in both editions offer proof that in reality Canto did not translate this volume. It was, instead, through his corrections of the first version, that the editor of Losada tried to give the false impression that this fifth volume had the same translator as the previous four.